The Child with Autism Spectrum Disorder: The Perceptions of Siblings. Issue 2 (17th June 2019) - Macedo Costa, Teresa; Pereira, Ana Paula da Silva
Abstract : This study sets out to understand and analyse the perceptions of six children regarding the Autism Spectrum Disorder of their brother or sister. The present research encompasses a qualitative interview method, from which semi‐structured interviews were carried out to participants ranging in ages from 10 to 12. The results of this study demonstrate that siblings, who have a high degree of knowledge and understanding about Autism Spectrum Disorder, feel less embarrassed and are better able to accept the challenges that this disorder causes. All participants indicate that: they have a solid and close relationship with their siblings, are more tolerant in the face of existing difficulties in their relationship; react negatively to the attitudes of others who are less understanding and tolerant; and are proud of their siblings with Autism Spectrum Disorder, for their progress and accomplishments. However, they continue to be unconditionally protective of their siblings in all situations.